Reconstructing a Culturally Grounded Social Entrepreneurship Model: Insights from Sundanese Cultural Values among Social Studies Education Students - Sari Handani, Sari; Maftuh, Bunyamin; Disman; Wiyanarti, Erlina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to identify forms of social entrepreneurship among Social Studies Education students, examine the application of Sundanese cultural values, analyze the supporting and inhibiting factors, and formulate a social entrepreneurship model based on local wisdom. A qualitative approach with a multiple-case study design was employed. The research was conducted at three universities—Universitas Bale Bandung, Institut Pendidikan Indonesia, and Universitas Tazkia—using observations, document analysis, focus group discussions (FGDs), and in-depth interviews with 29 informants, including students, faculty members, program administrators, and community partners. Data were analyzed interactively through data condensation, data display, and conclusion drawing. The findings indicate that student social entrepreneurship manifests in three main forms: businesses based on local potential, community cooperatives, and digital social movements. Sundanese cultural values, including Silih Asah, Silih Asih, Silih Asuh, Sauyunan, and Sabilulungan, as well as the character traits of Cageur, Bageur, Bener, Pinter, and Singer, were found to be well integrated into entrepreneurial practices. Institutional support and social capital emerged as the primary enabling factors, whereas limited financial capital and business literacy constituted the major barriers. This study resulted in the NISSE Model (Sundanese Values–Social Sciences–Social Entrepreneurship), a holistic framework that integrates cultural inputs, the pedagogical processes of Social Studies Education, student competencies, and community transformation. Theoretically, the model contributes to the theory of indigenous entrepreneurship by demonstrating how local wisdom can function as an operational principle shaping business ethics, collaborative decision-making, and altruistic orientations. Practically, the NISSE Model provides a curriculum framework for local-wisdom-based entrepreneurship that may be adapted to diverse cultural contexts globally.